Testing for Asymmetry in British, German and US Unemployment Data - Stephan Kohns (Institute for the Study of Labor (IZA), 2001)
Not only the level of aggregate unemployment but also the properties of its dynamics are an important topic in macroeconomics and labor economics. Several models like e.g. matching models with endogenous job destruction explicitly predict an asymmetric pattern in the evolution of unemployment, whereas linear models with Gaussian innovations preclude such dynamics. This paper applies several tests for asymmetry to aggregate British, German and US unemployment data to assess the relevance of asymmetries and compare the testing procedures. The results indicate that unemployment increases more quickly than it decreases, which is consistent with the pattern implied by matching models with endogenous job destruction.
Keywords: E32; J20; J64; 330; Asymmetries; unemployment dynamics; matching model; Arbeitslosigkeit; Konjunktur; Beschäftigungseffekt; Arbeitsmarkt; Matching; Schätzung; Großbritannien; Deutschland; USA